1989
DOI: 10.1063/1.456680
|View full text |Cite
|
Sign up to set email alerts
|

Photodissociation dynamics of water in the second absorption band. II. A bi n i t i o calculation of the absorption spectra for H2O and D2O and dynamical interpretation of ‘‘diffuse vibrational’’ structures

Abstract: We calculated the absorption spectra of H2O and D2O in the second absorption band around 128 nm using a two-dimensional ab initio potential energy surface for the B̃(1A1) electronic state. Nonadiabatic coupling to the lower states à and X̃ and the vibrational degree of freedom of the OH fragment are completely neglected. Despite these limitations the agreement with the measured spectra is very satisfactory. The overall shape, the width, and the energetical position of the maximum are well described. Most impo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
39
0

Year Published

1990
1990
2017
2017

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(44 citation statements)
references
References 41 publications
5
39
0
Order By: Relevance
“…[21][22][23][24][25] Due to the large torque along the dissociation path, the OH(X) fragment formed via non-adiabatic transitions was found to be rotationally excited, in agreement with experimental observations. These conclusions were confirmed by a later wavepacket study on three-dimensional PESs by van Harrevelt and van Hemert, 27, 31 who reported not only the absorption spectrum, but also ro-vibrational distributions of the OH fragments as well as the electronic branching ratio.…”
supporting
confidence: 76%
See 2 more Smart Citations
“…[21][22][23][24][25] Due to the large torque along the dissociation path, the OH(X) fragment formed via non-adiabatic transitions was found to be rotationally excited, in agreement with experimental observations. These conclusions were confirmed by a later wavepacket study on three-dimensional PESs by van Harrevelt and van Hemert, 27, 31 who reported not only the absorption spectrum, but also ro-vibrational distributions of the OH fragments as well as the electronic branching ratio.…”
supporting
confidence: 76%
“…As discussed before, these undulating peaks in the absorption spectrum stem from wavepacket recurrence in the Franck-Condon region. 21,22,31 In Fig. 2, we compare our calculated DCSs with those measured in a recent experiment.…”
mentioning
confidence: 94%
See 1 more Smart Citation
“…Several approximate twoand three-dimensional dynamical calculations, using either the adiabatic or the diabatic potential energy surfaces, have been reported. 8,9,19,[21][22][23][24][25] Whereas these studies have successfully explained the rotational distributions of OH(X 2 ⌸) and OH(A 2 ⌺ ϩ ), the calculated absorption spectra are not in satisfactory agreement with experiment, 12 and the relative fractions for different products OH(X), OH(A), H 2 ϩO( 1 D), and O( 3 P)ϩHϩH, have not yet been studied. A nonadiabatic treatment including all three internal coordinates is crucial to obtain even only qualitative agreement with experiments.…”
Section: Introductionmentioning
confidence: 85%
“…54,55 Note, however, that the anisotropy of the electronic B 1 A 1 state of water is very large around the angle γ ) 104°so that for the B r X transition the rotational degree of freedom cannot be neglected. 56,57 Let us assume that a wave packet in the state |g〉 is prepared. This can be achieved, for example, by strong-pulse infrared excitation or multiphoton transitions via excited electronic states, see section 3.…”
Section: Two-dimensional Revivalsmentioning
confidence: 99%